Multi-Objective Optimization of Rail Construction Project Management Using Immune Genetic Algorithms for Schedule, Cost, and Quality Trade-offs - Liu, Xiao (Informatica, 2025)
We address railway construction project management as a multi-objective optimization over schedule, cost, and quality. The proposed approach reformulates the tri-objective problem via a weighted-sum fitness